Screening for antioxidant capacity, pollen types and phytochemical profile by GC/MS and UHPLC from propolis - Ecem Bayram, Nesrin; Cevahir Öz, Gül (Progress in Nutrition, 2020)
Propolis is a resinous mixture collected by honeybees from different parts of plants such as poplars, birches, alders, conifers, pines, palms and willows. This study aims to determine pollen types (by light microscope), chemical compound profile (by GC-MS), fatty acid composition (by GC-MS), total phenolic content (by the Folin-Ciocalteu method), total flavonoid content (by the aluminium chloride method) and antioxidant capacity (by the CUPRAC, ABTS and CERAC methods) of a propolis sample from the western part of Istanbul, Turkey. As a result of microscopic analysis of the sample, pollen types of taxa belonging to 27 plant families were diagnosed. The GC-MS analysis of propolis revealed the presence of 38 phytochemical constituents that may contribute to its quality. Of these compounds, rates of “4H-1-benzopyran-4-one, 2,3-dihydro-5,7-dihydroxy-2-phenyl-,(S)” were highest. In addition, the concentrations of naringenin, pinocembrin and galangin were determined to be 2.45, 9.92 and 7.06 mg/ml by UHPLC analysis. The extract had significant antioxidant activity in all assays, with values of 282.8±9 mg TE /g in the CUPRAC, 425.7±18 mg TE/g in the CERAC and 186.4±8 mg TE/g in the ABTS assays. Antioxidant capacity of the propolis extract was positively associated with the total phenolic and flavonoid contents of the extract. Moreover, the major fatty acids were C20:1n9 (cis-11-eicosenoic acid), C22:1 (erucic acid) and C24:1 (nervonic acid). The results show that the propolis used in our study has important potential as an alternative food supplement and for cosmetic and therapeutic medicine and it can be used as an active agent in these areas.